Ø§Ù„ØªÙˆØ¬ÙŠÙ‡Ø§Øª Ø§Ù„Ù‚Ø±Ø¢Ù†ÙŠØ©: Ù…ÙÙ‡ÙˆÙ…Ù‡Ø§ ÙˆØ¯ÙˆØ±Ù‡Ø§ ÙÙŠ Ø§Ù„Ù…Ø¬ØªÙ…Ø¹ Ø§Ù„Ù…ØªØ¬Ø¯Ù‘Ø¯ - Ali, Nurul Badriyah Binti; Al-Athrasy, Radwan Jamal (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Da'wah of IAIN Langsa, 2017)
Quranic orientation has special abilities in showing people the right path and lead them in dealing with life matters perfectly from various aspects such as social, politic and economy. However, this orientation which is revealed by God had been neglected by Muslims, as well as its applications towards their life. Thus, this study aims to analyze the definiton of Quranic orientation and its main role in dealing with the changes of social challenges with continous development of life, in order to explain the significance of this orientation and its characteristics which able to be applied everytime and everywhere. This study used analysis method that leaded to some conclusions, among them: Quranic orientation is the guidance and direction that extracted from Al-Quran in fulfilling human?s needs that suitable in any circumtances and changes. The main role of Quranic orientation are: First, to extract its benefits to be a guideline for human being in any situations. Second, getting morals from the stories of Quran such as prophetic stories and the past peoples stories in order to meet contemporary challenges. Third, to be a proof to the authentication of Quran as God?s revelation and its reliability until the day of Judgement. Finally, to introduce Quranic orientation as the perfect and completed method and guideline to the human being.